From Marble to a Text Exoeskeleton: Formal Study of Three-dimensional Artworks Audiodescriptions - Álvarez de Morales Moreno, Candela (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study analyses audio descriptions (AD) of sculptures in six French museums as an accessibility tool for visually impaired individuals. Drawing on accessible translation theories, multimodality, and art research, it examines a corpus of 36 three-dimensional artworks, by evaluating their formal structure, content hierarchy, and clarity of the ADs according to international standards (Snyder, 2010; UNE 153020). The results reveal disparities in quality and coherence among museums, highlighting the need for standardized practices to ensure inclusion and accessibility in the cultural experience.